1988
DOI: 10.1002/esp.3290130406
|View full text |Cite
|
Sign up to set email alerts
|

Acid rain damage to carbonate stone: A quantitative assessment based on the aqueous geochemistry of rainfall runoff from stone

Abstract: An onsite experimental procedure was used to identify and quantify acid rain damage to carbonate stone, based on the change in rain runoff chemical composition. Observed changes in runoff from stone are attributed to the interaction of acidic species present in the rain with the stone surface. Onsite data obtained during the summer and fall of 1984 at three locations in the northeastern United States indicate that carbonate stone surface recession is related to acid deposition. Although the study is continuing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 18 publications
0
19
0
3
Order By: Relevance
“…More information can be obtained from the reaction paths/phase diagrams, by plotting the pairs of rainfall/run-off data on a diagram with axes of [Alk], which is the alkalinity, and [SO 4 2-]. This is because the carbonate dissolution model can be written as a linear combination of these two variables: Reddy (1988) in linear regression analyses. Because the precision of the chemical analysis of calcium in solution can be in the range of calcium in the run-off (due to acid rain), some acid rain indicators in the data may be lost in the noise.…”
Section: The Livingston Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…More information can be obtained from the reaction paths/phase diagrams, by plotting the pairs of rainfall/run-off data on a diagram with axes of [Alk], which is the alkalinity, and [SO 4 2-]. This is because the carbonate dissolution model can be written as a linear combination of these two variables: Reddy (1988) in linear regression analyses. Because the precision of the chemical analysis of calcium in solution can be in the range of calcium in the run-off (due to acid rain), some acid rain indicators in the data may be lost in the noise.…”
Section: The Livingston Modelmentioning
confidence: 99%
“…Material loss from carbonate stones that are exposed over a long period may be mainly a result of chemical attack, but also because of physical factors such as flaking, abrasion and cracking; whereas fresh limestones mostly loose material by chemical dissolution, particularly on rain-washed stones (Webb and others 1992). A direct estimate of the total mass released from a limestone during the process of rainwater running over its surface can be provided by the combination of microcatchment units (MCUs) and sensitive analytical methods (Livingston 1986;Reddy 1988). To quantify the effects of factors that control stone decay, several damage functions have been proposed for limestones based on insights into the dissolution process and/ or linear regression fits to large, experimentally obtained data sets (Lipfert 1989;Baedecker and others 1992;Butlin and others 1992;Kucera and Fitz 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Some experimental work corroborates this assumption. For example, Reddy (1988) compared the composition of incident rainfall to the composition of runoff from exposed marble and limestone surfaces. He found that surface recession (as calculated from increased Ca 2+ in the runoff) was strongly correlated with the amount of rainfall and its pH, and not strongly correlated with several other factors, including lithology.…”
Section: Theoretical Basismentioning
confidence: 99%
“…Pour expliquer ce phénomène, on ne peut qu'émettre des hypothèses. Reddy (1988) a en effet montré que l'agressivité de l'eau change rapidement suivant la lithologie sur laquelle elle ruisselle. Or, on sait que les nodules contiennent du mica, du feldspath, des pegmatites, du gneiss, des gabbros, etc.…”
Section: Nodules En Reliefunclassified